ترقية مهارة القراءة عبر أنشطة (Arabic Night) لدى الطلاب في معهد العقبة الواحد جومبانج - Paisal Paisal; Isniyatun Niswah (JURNAL AL-IHDA : Media Ilmiah Bahasa Arab, 2023)
Language is a window to the world and an opening tool (key) of a science is also a communication tool in the form of a sound symbol system produced by the human speech organ. Every human being will convey their intentions to other human beings through language. And the Arabic night activity is an Arabic language learning process that is provided to train reading skills, which aims as a process of improving reading skills for students. This study uses a qualitative method with a descriptive approach, Arabic night activities improve reading skills through Arabic Night activities for students, and Arabic Night activities are additional educational activities which are also excellent activities that focus on learning Arabic. The Arabic activity was held with the aim of being a driving factor to improve the reading ability of Al-Aqaba Islamic boarding school students located in the village of Kwaron, especially to read Arabic texts and more specifically to read the yellow book which has no recitation. The existence of is very helpful in the process of improving reading skills for all students.